EFEKTIVITAS PENGGUNAAN MEDIA GAMBAR SERI DALAM PEMBELAJARAN KETERAMPILAN MENULIS KARANGAN SEDERHANA KELAS III SD NEGERI WINONGO: kuantitatif eksperimen - Aurelia Putri Fatikasari; Sunarti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study seeks to assess the effectiveness of using a series of pictures in teaching third-grade students at Winongo State Elementary School in writing simple essays. This study employed a quantitative methodology employing a quasi-experimental design. Data collection was conducted through pre-tests and post-tests to evaluate simple essay writing skills before and after the intervention. The study sample consisted of two classes, III A and III B, at Winongo State Elementary School, which were allocated into an experimental group (undergoing treatment) and a control group (engaged in conventional learning). Prerequisite analysis included normality and homogeneity tests, while hypothesis analysis used an independent sample t-test. The results showed a significant difference in students' basic essay writing skills between the experimental and control groups, indicated by a significance value of 0.000 < 0.05. This suggests that the use of a series of pictures is beneficial in teaching simple essay writing skills to third-grade students. Therefore, the use of a series of pictures can be an efficient alternative medium for learning Indonesian, especially in writing simple compositions.